1972
DOI: 10.1103/physrevlett.28.497
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Ultraviolet Transmission of Crystalline and Amorphous Silicon

Abstract: The small polarization dependence of the fundamental Much attention has recently been given to the comparison of electronic-state densities in amorphous and crystalline solids. 1 ' 2 In this paper we present very high-resolution absorption spectra near the L m edge (photon energy 99.8 eV) of both amorphous and crystalline silicon. The observed spectrum for crystalline silicon is such that banddensity maxima, and even one or two critical points, can be identified upon comparison with band theory. The spectrum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
27
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(32 citation statements)
references
References 12 publications
5
27
0
Order By: Relevance
“…The theoretically calculated radius of the core exciton at the L 2,3 edge in bulk Si is $1.6 nm [93], which agrees well with measured X-ray absorption photon yield [89,94]. The radius of the elemental Si core of the NCs studied here is, at d/2 ¼ 1.1 AE 0.2 nm [71], substantially smaller than the core exciton radius, hence X-ray absorption in the silicon core at threshold should favor an excitonic final state more tightly bound than the corresponding bulk exciton.…”
Section: Xas Of Silicon Nanostructuressupporting
confidence: 73%
See 2 more Smart Citations
“…The theoretically calculated radius of the core exciton at the L 2,3 edge in bulk Si is $1.6 nm [93], which agrees well with measured X-ray absorption photon yield [89,94]. The radius of the elemental Si core of the NCs studied here is, at d/2 ¼ 1.1 AE 0.2 nm [71], substantially smaller than the core exciton radius, hence X-ray absorption in the silicon core at threshold should favor an excitonic final state more tightly bound than the corresponding bulk exciton.…”
Section: Xas Of Silicon Nanostructuressupporting
confidence: 73%
“…A broadening of absorption onset was observed by Eisebitt et al [87,88] in XAS from porous Si, and attributed to the crystallite size distribution in their samples. However, in the spectra shown in Figure 18, which are from a sample with a welldefined and narrow diameter distribution [71], a clear 0.61 eV spin-orbit splitting [89] is observed in the PPY from the NCs (magnified region of Figure 18, curve b), while such splitting may be washed out by the size inhomogeneity in the porous Si crystallites [87,88]. Single-dot luminescence spectroscopy has been used to study the emission line width of individual Si NCs and these studies have confirmed that oxidized NCs exhibit discrete energy levels rather than continuous bands [90].…”
Section: Xas Of Silicon Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The best illustration of the problem is provided by the Si L 2,3 edge, namely, transitions from the 2p core level (which is split into 2p 1͞2 and 2p 3͞2 levels) that the spectrum is a superposition of two virtually identical spectra separated by a small energy). When Brown and Rustgi [14] first reported the x-ray absorption (XAS) spectrum in 1972, they compared it with the calculated total conduction-band density of states (DOS) and noted that the latter could not account for the observations. The DOS exhibits a slow rise to a broad peak ϳ2 eV above threshold, whereas the observed spectrum exhibits a very steep rise and then a relative flattening.…”
mentioning
confidence: 98%
“…Thick curve: experiment (Ref. [14]); solid curve: full calculation including electron-hole interactions with a self-consistent hole orbital; dashed curve: calculation using the Z 1 1 model; dotted curve: calculation of excitation spectrum without electron-hole interactions; dash-dotted curve: effective-mass (parabolic band) spectrum without electron-hole interactions; long-dashed curve: effective-mass spectrum with hydrogenic excitonic effects as first done by Altarelli and Dexter (Ref. [4]).…”
mentioning
confidence: 99%